Legal Analysis of the Replacement of Retention Money with Retention Bond in Ongoing - Wibowo, Singgar Mataniari; Sami’an, Sami’an; Hardjomuljadi, Sarwono (International Journal of Law Policy and Governance, 2025)
Purpose –This study aims to analyze the legal basis related to Retention Money and Retention Bond in construction contract practices and provisions regarding the implementation of the transition from Retention Money to Retention Bond in ongoing contracts. Methodology/approach –This study uses a qualitative approach with analysis of contract documents, applicable legal regulations, and technical data related to the project. It also analyzes additional information obtained through previous literature reviews. Findings –In Retention Money, the Owner will directly withhold payment for the work until an agreed amount is reached, but in the development of construction this will certainly hinder the investment capabilities of the party implementing the work. Novelty/value –Considering the risks that may occur during the construction period, and ensuring the ability to carry out the work during the Defect Notification Period, retention is usually required. In its development, Retention Bond can be used to protect the Owner against the failure of the work implementer to perform after the work is carried out (Taking Over Certificate). Retention Bond can be constructed as an accessoir agreement, namely an additional or accompanying agreement and cannot stand alone without a preceding principal agreement.